Addressing Awareness and Affordability of Generic Medicines in India: A Data Driven Strategic Framework - Saurabh Kumar Banerjee; Moon Moon Lahiri; Devika Agarwal; Happy Agrawal (Journal of Multidisciplinary Applied Natural Science, 2025)
Access to quality and affordable generic medicines is vital to address the challenging situation which the country is currently facing in the present context. Less than 50% of medications are prescribed in India under their generic (INPN) names, despite the country being one of the leading suppliers of generic medications globally. Up to 90% of the money that impoverished people spend on healthcare can be attributed to medications. Thus, affordability of medications is essential for achieving desired treatment outcome since high drug costs lead to a reduction in access to healthcare. There is a lack of scientific data concerning the understanding of generic medicines among various stakeholders, including physicians, pharmacists, the general public, and health policy advocates, hence a need was felt to do an in-depth introspection of the scientific data centered around awareness and affordability of generic medicines in India and propose a conceptual framework for developing a strategic roadmap for popularizing generic medicines in India. Extensive literature search of research papers with high citations published between 2011–2024 were retrieved and investigated using PRISMA 2020 Flow diagram. In context to physicians the study suggested that physicians should choose less expensive brands of antibiotics and there is a need to design interventions at the fresh graduate level at medical colleges centered around the efficacy of generic drugs over the branded drugs. In context to Govt health policymakers the study suggested that policies towards opening Fair Price Medicine Shop (FPMS) taking the Government of West Bengal model could be taken into consideration and Pradhan Mantri Bhartiya Jan Aushadhi Pariyojana (PMBJP) drug policies on medicine distribution and procurement must be revisited with reference to the NELM. In context to pharmacists, community chemists regulatory agencies and educational institutions should work together to raise the level of generic drugs expertise among community chemists and drug store employees. Finally in context to patients, patient centric educational and awareness programs should be developed at the primary care level related to awareness and misconceptions of generic drugs in the public.